Factors Affecting Stadium Attendance in the Ghana Premier League amid High Social Media Consumption: A Study among Soccer Fans in Ghana - Kusi, Frank Appiah; Santiaguel, Emmanuel (Universitas Majalengka, 2024)
The recent attention to social media has altered the place of consumption of products and services in almost every sphere of business. The rise of social media has deepened the consumption of soccer, as it has brought on a new space for effective and convenient interactions, and engagement for sport fans. Thus, fans are been connected and linked to their favourite sport through social media with a sense of feeling and experience vis-à-vis their physical presence at the stadium. The purpose of this study was to investigate the factors contributing to low stadium attendance in the Ghana Premier League amid the high social media consumption of soccer among Ghanaians. The study adopted a quantitative method with a survey design via random sampling technique to gather data from 397 football fans in Accra, Kumasi and Ho. Validity and reliability of research instrument adopted the Lawshe’s content validity ratio, R and Cronbach Alpha, α which recorded R=0.86 and α=0.77 respectively. The study revealed factors such as poor leadership, officiating, Hooliganism/vandalism, club management, and advertisement and promotion of the league have affected stadium attendance among Ghanaian soccer fans. This has resulted in a switch to social media consumption to keep the spirit of their favourite sports alive and thereby been attracted to other leagues. This means that sponsors may not find the league attractive and this will affect league sponsorship.